THE SLOVAK YOUTH OPINION TO SENIORS SPORTING OPPORTUNITIES (Fiep Bulletin - online, 2014)
During the individual development of a human organism age-related changes occur in all organs and organ systems. We suggested analyzing the Slovak youth opinions to seniors sport participation in the occasion of The European Year for Active Ageing and Solidarity between Generations 2012 declared by European Commission. To obtain the students opinions we used a questionnaire method. The sample of 310 students of high schools and universities was represented by 226 men (73 %) and 83 women (27 %). The average age of the sample was 21.3 years. 61 % of our respondents were active sportsmen, 34 % are working as coaches, 15 % as a sports volunteer and 4 % were in the management positions. In the part of the questionnaire oriented to intergenerational solidarity, we asked our participants for their opinion to questions of discrimination. 44.5 % of respondents noticed the senior discrimination in job positions, 30.3 % intergenerational discrimination by young people, 40.6% in financial income, 19.4 % in social services and 21.9 % in the possibilities of exercises and physical activities. Most of the respondents considered as the most important step to optimize and reform the physical activity possibilities for seniors the interest of state authorities (60 %), organized regular exercises for seniors (58.7 %) and wider range of appropriate senior physical activities and sports. We appreciate the fact that 62.3 % respondents are willing to engage and participate in different intergenerational physical activity.
Keywords: senior physical activities; intergenerational solidarity; senior discrimination; sport between generations